(untitled) (Indian Journal of Geo-Marine Sciences (IJMS), 2025)
Gayralia oxysperma (Kützing) K.L. Vinogradova ex Scagel et al. 1989, Doty, (Monostromataceae, Ulvales) possesses exceptional nutritional, antioxidant, and medicinal properties, thriving in fluctuating saline environments and demonstrating resilience against salt stress due to its rich composition of nutrients and phytochemicals. This is an estuarine form of seaweed and is subjected to intense salinity regimes, particularly during the monsoon period (June – September). Therefore, the present study was undertaken to investigate the changes in growth and some cellular biochemical constituents of G. oxysperma following exposure to selected salinities viz. l.6 ‰, 4.8 ‰, 8 ‰, 16 ‰, and 32 ‰ in the laboratory culture. The growth of fronds increased with increasing salinity and showed an optimum growth of 2.5-fold increase over initial biomass in 1.6 ‰ on day 15. The microscopic observation of fronds from lower salinity showed unevenly distributed elongated cells with low density and large intercellular spaces. In contrast, at a higher range (> 8 ‰), cells were more compact and evenly distributed all over the thallus. The chlorophyll content increased to 2.8-fold in 32 ‰ over the initial salinity of 1.6 ‰. Proline content of fronds cultured in 32 ‰ showed 9.5-fold increase compared to 1.6 ‰ salinity. Similarly, glycinebetaine also increased with salinity (32 ‰) and showed 2.3-fold increases over values obtained for 1.6 ‰. These findings suggest that G. oxysperma thalli accumulate a high amount of osmolytes like proline and glycinebetaine to sustain during adverse salinity stress conditions.